2019
DOI: 10.9758/cpn.2019.17.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health Literacy and Health-related Behaviors in Patients with Psychosis

Abstract: Objective This study compared the levels of knowledge of physical illnesses and patterns of health behaviors between patients with psychosis and the general population. Methods A total of 712 participants were included in the study; 292 patients with a schizophrenia spectrum disorder and 420 healthy controls matched for age and gender. Questionnaires were administered to study participants to determine the level of knowledge of chronic physical illnesses such as cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…It has been suggested that individuals with serious mental illness may be especially at risk for coronavirus exposure and infection (Shinn and Viron, 2020). In particular, the effects of factors such as socioeconomic disadvantage and lower health literacy, as manifest in a lack of understanding of preventive health behaviors (Kim et al, 2019; Shinn and Viron, 2020), may be compounded by specific characteristics associated with mental disorders, such as hopelessness, that may hinder adherence to necessary health behaviors (Gehi et al, 2005). Difficulty in undertaking COVID-19-related preventive behaviors among those with mental health problems may have been further exacerbated during the ongoing pandemic by the novel nature of the disease itself, and the plethora of information (‘infodemic’) it has generated, both in conventional and social media, that has resulted in uncertainty and worry (Fiorillo and Gorwood, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that individuals with serious mental illness may be especially at risk for coronavirus exposure and infection (Shinn and Viron, 2020). In particular, the effects of factors such as socioeconomic disadvantage and lower health literacy, as manifest in a lack of understanding of preventive health behaviors (Kim et al, 2019; Shinn and Viron, 2020), may be compounded by specific characteristics associated with mental disorders, such as hopelessness, that may hinder adherence to necessary health behaviors (Gehi et al, 2005). Difficulty in undertaking COVID-19-related preventive behaviors among those with mental health problems may have been further exacerbated during the ongoing pandemic by the novel nature of the disease itself, and the plethora of information (‘infodemic’) it has generated, both in conventional and social media, that has resulted in uncertainty and worry (Fiorillo and Gorwood, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both SMI and AUD are associated with important cognitive deficits, including executive dysfunction, making these patients more prone to impairments in goal formation, planning, attention, inhibition of response, or coordinating complex cognition. 24 , 25 In addition, people with SMI and AUD comprise a marginalized group 26 , 27 with lower educational attainment 28 , 29 and health literacy 30 , 31 on average, compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to definitively determine whether these associations are primary or secondary, given that psychiatric patients are known to have lower levels of health literacy, poorer physical health outcomes, and quality of life and that numerous psychotropic medications have significant side effects of weight gain. 5,55 57 The prevalence of smoking has been shown to be higher in psychiatric populations, 58 which may account for the higher incidence of obstructive lung disease seen in this patient population. A very recent study demonstrated that psychiatric patients, particularly men with schizophrenia spectrum disorders and obesity, are at increased risk of obstructive sleep apnea and suggested that screening for obstructive sleep apnea should be mandatory in this patient population.…”
Section: Discussionmentioning
confidence: 99%